2012
DOI: 10.1140/epja/i2012-12008-7
|View full text |Cite
|
Sign up to set email alerts
|

Shallow-underground accelerator sites for nuclear astrophysics: Is the background low enough?

Abstract: Abstract. In order to reliably estimate the rate of a charged particle induced nuclear reaction in a nonexplosive astrophysical scenario, its cross-section must be measured far below the Coulomb barrier. However, at the corresponding energies the cross-section values are very low, so that the experimental counting rate is dominated by cosmic-ray induced background, even if a suitable anticoincidence shield is applied. This problem can be overcome by performing an accelerator-based experiment in a deep undergro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 47 publications
(48 reference statements)
2
27
0
Order By: Relevance
“…Background intercomparison using one and the same escape-suppressed HPGe detector, subsequently transported to different sites. The data [16,17] show that using a muon veto, the Felsenkeller background is not far from the deep underground (Gran Sasso) case.…”
Section: Background Studiesmentioning
confidence: 94%
See 3 more Smart Citations
“…Background intercomparison using one and the same escape-suppressed HPGe detector, subsequently transported to different sites. The data [16,17] show that using a muon veto, the Felsenkeller background is not far from the deep underground (Gran Sasso) case.…”
Section: Background Studiesmentioning
confidence: 94%
“…Detailed measurements at Felsenkeller [16,17] have shown that the background in the crucial 7-8 MeV γ-energy range (affecting inter alia the 12 C(α, γ) 16 O reaction) is only a factor of 3 higher in Felsenkeller than deep underground at Gran Sasso (Figure 1). …”
Section: Background Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This system was moved successively to several sites. The data show that with a muon veto, the background in the 6-8 MeV energy region is only a factor of 2-4 higher in Felsenkeller than deep underground at LUNA, enabling highly sensitive experiments [14]. The exercise was repeated with a 3" LaBr 3 detector, and again the background in Felsenkeller was less than one order of magnitude higher than deep underground at LUNA, if a muon veto was used [14].…”
Section: Site Status and Background Studiesmentioning
confidence: 97%